2021
DOI: 10.1093/geronb/gbab132
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement From COVID-19, Gender, and Reports of Depression Among Older Adults in Europe

Abstract: Objectives The COVID-19 pandemic has left older adults around the world bereaved by the sudden death of relatives and friends. We examine if COVID-19 bereavement corresponds with older adults’ reporting depression in 27 countries, and test for variation by gender and country context. Methods We analyze SHARE COVID-19 data collected between June-August 2020 from N=51,383 older adults (age 50–104) living in 27 countries, of who… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…38,39 Rates of domestic and gender-based violence and abuse have also reportedly increased during lockdowns. 40,41 Moreover, recent evidence suggests that, in addition to first-hand bereavements through the loss of loved ones during the pandemic, the mental health of women aged 50 and older may have also been affected by the collective, larger-scale death toll of the pandemic, 42 which in the UK remains one of the highest in Europe. 43 These different factors may partly explain the larger disruption of the pre-existing long-term distress trajectories experienced by women during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Rates of domestic and gender-based violence and abuse have also reportedly increased during lockdowns. 40,41 Moreover, recent evidence suggests that, in addition to first-hand bereavements through the loss of loved ones during the pandemic, the mental health of women aged 50 and older may have also been affected by the collective, larger-scale death toll of the pandemic, 42 which in the UK remains one of the highest in Europe. 43 These different factors may partly explain the larger disruption of the pre-existing long-term distress trajectories experienced by women during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence prior to the pandemic using data from the British birth cohorts has shown that, throughout adulthood, there seems to exist an upwards trend in the long-term psychological distress trajectories by middle age (age [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], and a decrease towards older age. 14,15 By extending these analyses to include data collected during the first year after the COVID-19 pandemic onset, we aims to understand whether the changes in distress reflect a continuation or an alteration/disruption of these pre-pandemic trends, which may have implications for future trends of morbidity, disability, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“… Wang et al (2021) compared older adults across Europe finding that, independent of having lost a friend or relative to COVID-19, living in a country with a high death rate from the virus led to increases in depression among older women. The independent impact of societal death rates on mental health draws attention to the contextual cues of the pandemic.…”
Section: Covid-19 Bereavementmentioning
confidence: 99%
“…Still others designed COVID-19-specific studies such as the Fuller and Huseth-Zosel (2021) study of older adults in the urban and rural regions of the Midwest United States. These studies cover a broad range of topics such as the economic precarity due to furloughs and job loss ( Abrams et al, 2021 ; Choi et al, 2020 ; Taylor et al, 2021 ), loss of loved ones to the COVID-19 virus ( Lin & Liu, 2021 ; Wang et al, 2021 ), and downstream impact of extended loneliness and isolation ( Freedman et al, 2021 ; Robbins et al, 2021 ). Below, I briefly comment on the major themes that coalesce in this issue.…”
mentioning
confidence: 99%
“…Each US COVID-19 death leaves nine close kin bereaved ( 3 ), including 0.078 children aged 0 to 17 y experiencing parental bereavement ( 4 ), and the pandemic has resulted in over 1 million new orphans under age 18 y globally as of May 2021 ( 5 ). This will have important population health and welfare implications given the known negative consequences of kin loss, including declines in physical and mental health and the loss of social and economic support ( 6 8 ). What remains to be better understood, however, is how these increases in population-wide bereavement shape individual-level risks of losing relatives—by how much does the incidence of kin loss increase in periods of high excess mortality, and which demographic groups are likely to be affected?…”
mentioning
confidence: 99%